ROLE OF LIVER SINUSOIDAL CELLS AND BONE MARROW CELLS IN REALIZATION OF REGENERATIVE STRATEGY OF NORMAL AND DAMAGED LIVER - A. V. Lyundup; N. A. Onishchenko; M. E. Krasheninnikov; M. Y. Shagidulin (Вестник трансплантологии и искусственных органов, 2010)
Sinusoidal cells play the key role at all kinds of liver regeneration (physiological, reparative, fibrogenetic), which vector depends on adaptative reserves of these cells (first of all Ito cells) stressful damaging factors affect. It was demonstrated that under reparative liver regeneration the recovery of hepatocytes pool originates not only from mitosis, but from regional stem cells – oval cells, Ito cells and from migrating bone marrow cells. Fibrogenetic liver regeneration occurs as a result of inhibiting stem cell function of Ito cells and bone marrow cells.